Reliability and sensitivity of nocturnal heart rate and heart-rate variability in monitoring individual responses to training load - Nuuttila, O. P.; Seipäjärvi, S.; Kyröläinen, H.; Nummela, A. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To assess the reliability of nocturnal heart rate (HR) and HR variability (HRV) and to analyze the sensitivity of these markers to maximal endurance exercise.